Detection of knee wobbling as a screen to identify athletes who may be at high risk for ACL injury. Issue 1 (1st January 2021) - Aoki, Akino; Kubota, Satoshi; Morinaga, Kosuke; Zheng, Naiquan Nigel; Wang, Shangcheng Sam; Gamada, Kazuyoshi
ABSTRACT: This study developed a method to detect knee wobbling (KW) at low knee flexion. KW consists of quick uncontrollable medio-lateral knee movements without knee flexion, which may indicate a risk of ACL injury. Ten female athletes were recorded while performing slow, single-leg squats. Using motion capture data, the ratio of the frontal angular velocity to sagittal angular velocity (F/S) was calculated. An 'F/S spike' was defined when the F/S ratio exceeded 100%. The number of F/S spikes was counted before and after low-pass filtering at different cut-off frequencies. Intraclass correlation coefficients for KW and filtered F/S spike were analysed. KWs per squat cycle showed a median (range) of 3 (2–8) times. F/S spikes before and after low-pass filtering at 3-, 6-, 10-, and 15-Hz were 51 (12–108), 2 (0–6), 3 (1–12), 5 (2–21), and 9 (3–33) times, respectively. KWs and F/S spikes on motion capture with 6-Hz, low-pass filtering were well correlated ( r = 0 .76). Median percentages of valgus and varus F/S spikes were 71% and 29%, respectively. After 6Hz, low-pass filtering, the number of F/S spikes was strongly correlated with observed KWs. An F/S spike assessment may be used to objectively detect KW, including flexion and varus/valgus angular velocity.